Glúten: ocorrência em alimentos industrializados e monitoramento da aplicação da Lei 10.674 de 2003. - Cristiane Lúcia Goddard (2016)
In order to evaluate the agreement of the analytical result with the labeling statements on processed foods and verify the application of Law 10,674 of 2003, which requires that food products sold inform about the presence of gluten, as a preventive and control measure for celiac disease, gluten content was determined in 245 products, from 15 categories, primarily with the declaration “Does not contain gluten”, between March 2015 and September 2016. The performance of the standardized immunoenzymatic method of the Association of Official Analytical Chemists – AOAC was evaluated based on veracity, limit of quantification, repeatability and intermediate precision. The measurement uncertainty of the method was estimated by summing the individual contributions of the sources. The analytical results were compared with the declaration of the presence or absence of gluten on the label and with the list of ingredients present on the product labels. The inclusion of warning phrases and the use of other expressions not provided for in current legislation were also observed. It was found that 235 samples (95.9%) had gluten levels below the detection limit of 5 mg/kg. Non-compliance with Law 10,674/2003 could be seen in 54 samples (22.0%) in the following cases: in five samples of corn flour and cornmeal there was no declaration of the presence or absence of gluten; in 26 samples of tapioca starch biscuits, gluten-free biscuits, gluten-free pasta and tapioca, the use of expressions not provided for in the Law was identified, such as “Gluten-free”, “Gluten-free” and “Suitable for celiac patients”; in 21 samples, the declaration “Contains gluten” was presented, even without containing a source ingredient and in disagreement with the analytical gluten content, and in two samples of ready-made seasonings, from different brands, there was the declaration “Does not contain gluten”, but these presented gluten levels of 16 and 37 mg/kg, representing a risk for celiac consumers. It was concluded that the proposed method was suitable for the purpose of quantifying gluten, that more than 99% of foods that declare “Does not contain gluten” were safe for consumption by celiac patients, and that manufacturers must adapt to the provisions of Law 10,674 /2003 and that continued monitoring is necessary with the inclusion of other food categories to guarantee the safety of celiac consumers.